Fracturability and morphology of broiler chicken femurs as determinants of luminosity - Carazo-Chanto, Joyce (2026)
The present study, conducted in Costa Rica from January to December 2015, investigated the relationship between femur luminosity (L*) in broiler chickens and femur thickness, length, and breaking strength. A total of 651 femurs were sampled at a poultry processing plant in Siquiares, Alajuela, originating from 10 poultry farms. Luminosity measurements were performed at the end of the chilling process and, subsequently, after deboning using a Minolta colorimeter. Thickness (mm) and length (mm) were measured using a digital caliper. The femurs were subsequently transported to LANAMME at the University of Costa Rica, where breaking strength (kgf) was measured using an MTS Landmark universal testing machine. The results were analyzed using Welch’s ANOVA, 95% confidence intervals, Spearman’s correlations, robust multiple linear regression, and principal component analysis (PCA). Welch’s ANOVA showed significant differences in mean L* among some farms (p < 0.05); however, mean values for all  farms remained within the acceptable category according to the DSM® scale (L* > 40). In all farms, at least 93% of the bones exhibited acceptable luminosity (lower limit of the 95% CI ≥ 0.93). Spearman’s correlations were significant between L* and the other variables evaluated (ρ < 0.05). The linear regression model explained 17.1% of the variability in L* (R² = 0.171, p < 0.001), with breaking strength being the most influential predictor. Principal component analysis (KMO = 0.753; Bartlett’s test, p < 0.001) extracted a single principal component (λ₁ = 2.270), which explained 56.76% of the total variance, with generally high variable loadings (≥ 0.60). It is concluded that femurs with greater post-processing luminosity are associated with parameters indicative of better bone integrity.